Leadless pacemaker implantation and concurrent atrioventricular junction ablation in patients with atrial fibrillation. Issue 5 (16th April 2018) - Okabe, Toshimasa; El‐Chami, Mikhael F.; Lloyd, Michael S.; Buck, Benjamin; Gornick, Charles C.; Moore, JoEllyn C.; Augostini, Ralph S.; Hummel, John D.
Abstract: Background: Atrioventricular junctional (AVJ) ablation and pacemaker implantation are indicated when pharmacotherapy fails to achieve adequate rate control in atrial fibrillation (AF). The purpose of our study is to assess the feasibility and safety of concurrent Micra leadless transcatheter pacemaker implantation and AVJ ablation. Methods: We retrospectively assessed patients who underwent Micra implantation and concurrent AVJ ablation at three institutions between August 2014 and March 2016. All patients and devices were followed at baseline and at 1, 3, 6, and 12 months postimplantion. Results: Twenty‐one patients with permanent AF (median age 77 [range: 62–88], female 15 [71.4%]) underwent successful Micra implantation followed by concurrent AVJ ablation. There was no device dislodgement or malfunction during the 12‐month follow‐up. Complete 12‐month electrical performance data were available in 14 patients (67%). Among patients with the complete data set, median pacing thresholds at implant and at 1, 3, 6, and 12 months were 0.5 V (range: 0.25–0.88), 0.44 V (range: 0.25–2.0), 0.5 V (range: 0.25–1.63), 0.5 V (range: 0.25–1.13), and 0.5 V (range: 0.25–1.13) at a pulse width of 0.24 msec, respectively. Two patients died due to noncardiac causes during follow‐up. There were no patients with major device‐related complications. Conclusions: Concurrent Micra implantation and AVJ ablation is feasible and appears safe. There was no device dislodgement, malfunction, or significant pacing threshold rise requiring device reimplantation during the 12‐month follow‐up. This combined approach can be considered for patients with AF with suboptimal rate control who have failed AF catheter ablation and/or pharmacotherapy.